2022
DOI: 10.1038/s41467-022-30868-6
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal adipose afferent nerves sustain pathological high blood pressure in rats

Abstract: Hypertension is a pathological condition of persistent high blood pressure (BP) of which the underlying neural mechanisms remain obscure. Here, we show that the afferent nerves in perirenal adipose tissue (PRAT) contribute to maintain pathological high BP, without affecting physiological BP. Bilateral PRAT ablation or denervation leads to a long-term reduction of high BP in spontaneous hypertensive rats (SHR), but has no effect on normal BP in control rats. Further, gain- and loss-of-function and neuron transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Cumulating evidence showed that perirenal adipose tissue (PRAT) was significantly associated with high BP [ 7 9 ] Recently, it was revealed that perirenal adipose afferent nerves played a key role in sustaining pathological high BP in rats [ 10 ]. Long-term reduction of BP was observed in spontaneously hypertensive rats by bilateral PRAT ablation [ 10 ]. Thus, we hypothesize that the PRAT can be a potential target for lowing BP in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulating evidence showed that perirenal adipose tissue (PRAT) was significantly associated with high BP [ 7 9 ] Recently, it was revealed that perirenal adipose afferent nerves played a key role in sustaining pathological high BP in rats [ 10 ]. Long-term reduction of BP was observed in spontaneously hypertensive rats by bilateral PRAT ablation [ 10 ]. Thus, we hypothesize that the PRAT can be a potential target for lowing BP in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, observational studies failed to clari ed the pathological mechanism of hypertension caused by perirenal fat. Recently, researchers nd that bilateral perirenal fat ablation leads to a long-term reduction of high blood pressure in spontaneous hypertensive rats, and has no in uences on normal blood pressure in control rats, they further indicate that perirenal afferent nerves serve as a pathological node of hypertension that sustains elevated blood pressure via suppressing CGRP, thereby being a potential therapeutic target to tackle primary hypertension [10]. And the perirenal fat is so distinguished that no other fat pad such as inguinal, pararenal or epididymal adipose tissue, is associated with the maintenance of high blood pressure in their research.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, perirenal fat is a unique connected tissue that is well vascularized and innervated [7]. Cumulating evidence showed that perirenal adipose tissue (PRAT) was signi cantly associated with high BP [7][8][9] Recently, it was revealed that perirenal adipose afferent nerves played a key role in sustaining pathological high BP in rats [10]. Long-term reduction of BP was observed in spontaneous hypertensive rats by bilateral PRAT ablation [10].…”
Section: Introduction Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, leptin production in the depot was decreased, a protein implicated in the development of glomerulosclerosis (59). Decreased leptin interaction with afferent nerves within perirenal fat may explain the decrease in kidney sympathetic nerve activity associated with SGLT2is (60,61). PPAR- δ , peroxisome proliferator–activated receptor- δ .…”
Section: Mechanisms Of Kidney Protectionmentioning
confidence: 99%